Rapid detection in spinal fluid of beta-lactamase produced by ampicillin-resistant Haemophilus influenzae. - Boughton, W H (1982)
The chromogenic cephalosporin nitrocefin was used to detect the presence of beta-lactamase in cerebrospinal fluid of patients suffering from ampicillin-resistant Haemophilus influenzae meningitis. Five samples of spinal fluid containing ampicillin-resistant isolates were studied, and all had beta-lactamase activity. When samples of spinal fluid containing 33 ampicillin-sensitive isolates and 234 sterile specimens were tested, no beta-lactamase activity was detected.